Droplet-based microfluidic platform for protein crystallization - Ferreira, Joana (2017)
[Excerpt] The main focus of protein crystallization has been in the production of high-quality protein crystals for 3D structure determination by X-ray diffraction. However, this is a complex and multiparametric process, involving thermodynamic and kinetic features, as well as the optimization of several variables, where there is not an accurate theory to substitute for empirical approaches (Giegé and McPherson 2006). In this context, droplet-based microfluidics allows the generation of hundreds of droplets, each one acting as a microreactor, enabling thus to perform high-throughput screening of protein crystallization experiments under identical conditions.